Ketorolac Use for Pain Management in Trauma Patients With Rib Fractures Does not Increase of Acute Kidney Injury or Incidence of Bleeding. Issue 5 (May 2021) - Torabi, Julia; Kaban, Jody M.; Lewis, Erin; Laikhram, Dana; Simon, Rachel; DeHaan, Skylar; Jureller, Michael; Chao, Edward; Reddy, Srinivas H.; Stone, Melvin E.
Introduction: Ketorolac is useful in acute pain management to avoid opiate-related complications; however, some surgeons fear associated acute kidney injury (AKI) and bleeding despite a paucity of literature on ketorolac use in trauma patients. We hypothesized that our institution's use of intravenous ketorolac for rib fracture pain management did not increase the incidence of bleeding or AKI. Methods: Rib fracture patients aged 15 years and above admitted between January 2016-June 2018 were identified in our trauma registry along with frequency of bleeding events. AKI was defined as ≥ 1.5x increase in serum creatinine from baseline measured on the second day of admission (after 24 hours of resuscitation) or an increase of ≥ .3 mg/dL over a 48-hour period. Patients receiving ketorolac were compared to patients with no ketorolac use. Results: Two cohorts of 199 control and 205 ketorolac patients were found to be similar in age, gender, admission systolic blood pressure (SBP), injury severity score, intravenous radiocontrast received, and transfusion requirements. Analysis revealed no difference in frequency of AKI using both definitions (8% vs. 7.3%, P = .79) and (19.6% vs. 15.1%, P = .24), respectively, or bleeding events (2.5% vs. 0%, P = .03). Logistic regression demonstrated that ketorolac use was not an independent predictor for AKI but age and admission SBP < 90 were. Conclusion: Use of ketorolac in this cohort of trauma patients with rib fractures did not increase the incidence of AKI or bleeding events.